Epigenome-wide Association Study of Diet Quality in the Women's Health Initiative (OR31-06-19). (13th June 2019) - Leet, R Whitney; Whitsel, Eric; Staimez, Lisa; Horvath, Steve; Assimes, Themistocles; Bhatti, Parveen; Jordahl, Kristina; Narayan, K M.Venkat; Conneely, Karen
Abstract: Objectives: This study examined the influence of diet on the methylome by analyzing 428, 019 cytosine-guanine nucleotide pair (CpG) sites and assessing whether diet quality was associated with differential methylation patterns. Methods: The study population included 4529 women from the Women's Health Initiative (WHI) observation and clinical trial from three ancillary studies: EMPC, BAA23, and AS311. DNA methylation was measured from whole blood samples using the Illumina Infinium HumanMethylation450 Beadchip. Diet quality was assessed using the Alternative Healthy Eating Index 2010 (AHEI-2010). An epigenome-wide association study (EWAS) meta-analysis, stratified by study cohort, was done using generalized linear models by regressing methylation β values (β = Methylated probes/[Methylated + Unmethylated probes]) for each CpG site on the primary exposure, AHEI, adjusting for cell composition, chip number and location, study characteristics, principle components of genetic relatedness, age, ethnicity and BMI. Significance was set at Holm-Bonferroni P  < 0.05. Results: Demographic characteristics are described by quartile of AHEI with Quartile 4 equivalent to the healthiest diet (highest score) and Quartile 1 equivalent to the poorest diet (lowest score) in Table 1. We found diet quality was significantly associated with 340 CpG sites after false discovery correction (Figure 1). While statistically significant, effect sizes were small (∼0.0003). These findings suggest that, on average, as AHEI increases by one SD (10.1 units), methylation changes by only ±0.003 in associated CpG sites. When examining the top 20 CpG sites (Table 2), several sites were located in genes critical to metabolism, including cg26137868 in the FOXA2 gene and cg20006924 in the RORA gene, both related to the regulation of glucose and fat metabolism and 3 CpG sites in the SLC18A2, SLC2A14, and SLC16A3 genes related to nutrient transport. Conclusions: This is the first reported EWAS examining the relationship between diet quality and methylation in humans. While diet quality was statistically associated with many CpG sites, the effect sizes were small. Further investigation is required to understand the relationship between diet quality and the methylome. Funding Sources: NA. Supporting Tables, Images and/or Graphs: